2021
DOI: 10.20360/langandlit29502
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Literacy and Positive Identity Negotiations with Multimodal Comic Composing

Abstract: This study explores how an alternative writing unit with a focus on comics, choice, and publishing supported positive identity development in a fourth-grade classroom. Many traditional literacy practices with an emphasis on skills marginalize students from under-represented populations. This study reports literacy practices that countered the production of previously established unequal relationships and instead supported bilingual students’ negotiation of positive identities. We conducted an analysis of two b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It is even more critical for teacher candidates to be exposed to, work with, critically evaluate, and create multimodal texts such as visual journals. They will be expected to comprehend an ever-evolving understanding of literacy alongside with meaningful pedagogy that involves both online and offline practices (Laidlaw et al, 2021;Moses & Reid, 2021;Nagy, 2020;Yoon, 2020). This literacy, according to the Ontario Ministry of Education ( 2013) is "multimodal" (p. 2), builds on "prior knowledge and culture" (p. 3), is "rich and varied" (p. 3), and utilizes all six dimensions of language (reading, writing, listening, speaking, viewing, and representing).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is even more critical for teacher candidates to be exposed to, work with, critically evaluate, and create multimodal texts such as visual journals. They will be expected to comprehend an ever-evolving understanding of literacy alongside with meaningful pedagogy that involves both online and offline practices (Laidlaw et al, 2021;Moses & Reid, 2021;Nagy, 2020;Yoon, 2020). This literacy, according to the Ontario Ministry of Education ( 2013) is "multimodal" (p. 2), builds on "prior knowledge and culture" (p. 3), is "rich and varied" (p. 3), and utilizes all six dimensions of language (reading, writing, listening, speaking, viewing, and representing).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pedagogical opportunities at the heart of this framework are ripe for new lenses as we consider how modes and media continue to change in response to global and local needs. Multimodal meaning making opportunities are meant to scaffold, reinvent, and transform knowledge as well as individuals (Loerts & Heydon, 2016;Moses & Reid, 2021;Walsh, 2007). While the term, visual journals, is used in this research, the range of modalities including visual modalities were used to give the participants choice in what was most apt for their multimodal ensembles.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Honoring multiple modes and different kinds of representational work may also help teachers reconceptualize what counts as reading and writing in schools. For example, researchers have documented ways in which multimodal curriculum units provided opportunities for emergent bilinguals and students with disabilities to renegotiate their identities and positioning in the classroom (Moses & Reid, 2021; Reid & Moses, 2021). Vasudevan et al (2010) showed how multimodal composing opportunities made it possible for fifth-graders to author new literate identities or authorial stances.…”
mentioning
confidence: 99%
“…They then demonstrated their knowledge of how images and words might work together in print narratives through multimodal composition. The broader study documented the instructional practices and students’ use of a wide range of semiotic resources (Moses & Reid, 2021; Reid & Moses, 2020). However, those findings provide a generalized overview of all students but lack the in-depth analysis of a single comic.…”
mentioning
confidence: 99%
“…Collectively, we have examined how graphic novel adaptations of young adult novels represent the narratives and position readers differently (Kachorsky & Reid, 2020). Stephanie has focused on reading and composing comics in elementary grades and has explored how some students were able to position themselves differently when representing and communicating narrative through the comics medium (Moses & Reid, 2021;Reid & Moses, 2020).…”
mentioning
confidence: 99%